Identifying disclosure items for Zakat institutions - Puat Nelson, Sherliza; Sapingi, Raedah; Ahmad, Maslina (2017)
The purpose of this study is to develop disclosure items as research instruments, which may be used for future research to measure disclosure level among zakat institutions. The process involved four prevalent stages, from determining disclosure items from various literature, to panels of experts’ reviews, pilot survey, and questionnaire survey. All the necessary reliability and validity tests were carried out to come up with the final zakat disclosure items, necessary to be included among zakat institutions’ annual reports. The disclosure items were categorised accordingly following their theme.